A new geodatabase of fuel treatments across federal lands in the USA - Call, Anson, author; Tomczyk, Nathan, author; Withnall, Katahdin A., author; Dappen, Patricia R., author; Heusinkveld, Dana, author; Mueller, Stephanie, author; Holloway, Ben, author; Shennan, Keaton, author; Herring, Jennifer, author; Franko, Aidan, author; Colavito, Melanie M., author; Kimple, Aaron D. author; et al. (Colorado State University. Libraries, 2025)
Catastrophic wildfires threaten landscapes across the United States, and fuel treatments are key to mitigating this risk. Yet, information regarding when, where, and what types of treatments have occurred is scattered across multiple systems of record. Limited accessibility and utility of these data have impeded the coordinated tracking of treatment implementation and assessment of treatment effectiveness. Here, we present the Treatment and Wildfire Interagency Geodatabase (TWIG): a database that combines fuel treatment data from the U.S. Forest Service and U.S. Department of the Interior systems of record, making them easily accessible and interpretable. TWIG aims to provide the most complete nationwide database of fuel treatments, offering a wide range of land management, policymaking, and research applications.
Keywords: environmental impact; fire ecology; forest ecology; forestry; Treatment and Wildfire Interagency Geodatabase (TWIG)